Analysis of Financial Technology and Green Marketing On Brand Loyalty (Study Case on Starbucks Multatuli Medan Branch): Analisis Pengaruh Teknologi Finansial dan Pemasaran Hijau terhadap Loyalitas Merek (Studi Kasus Starbucks Cabang Multatuli Medan) - Elbert Lie; Desma Erica Maryati Manik (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
In today's digital world, alongside worldwide problems like environmental harm from human actions and rising global temperatures, there's a growing understanding of the need to protect our environment. The extensive reporting on waste-related issues has captured widespread attention, leading to heightened public worry and greater environmental consciousness. This situation has motivated businesses to actively participate in environmental preservation efforts, working alongside the community. This research seeks to determine how financial technology impacts brand loyalty, to explore green marketing's effect on brand loyalty, and to assess the combined effect of financial technology and green marketing on brand loyalty. This study will survey all Starbucks customers in 2024, using a sample group of 160 individuals, obtained using Hair et al collected using questionnaire. The study's findings indicate that both financial technology and green marketing independently influence brand loyalty to some extent, and that together, they have a combined impact on brand loyalty partially or simultaneously.